The Role of the Serbian Church in Maintaining National Identity of the Serbian Nation under Turkish Rule - Суботин-Голубовиħ, Татьяна (Poznańskie Studia Slawistyczne, 2013)
The re-establishment of the autocephality of the Serbian Church in 1557 instigated a considerable degree of activity in the field of cultural restoration. The see of the Patriarchate was revived in its former location – in the monastery Peć. Restoration of the structures of the church organization was accompanied by reparation of the old (abandoned or neglected) churches and monasteries, as well as by building of new objects. A number of new churches and monasteries arouse in the regions of the Balkans which were colonized by Serbs intensively and systematically. The new churches required liturgical books necessary for non-hindered performance of the rite. The result was that old scriptoria were restoring and intensifing their activity, but at the same time new scriptoria started to fill the libraries of numerous churches and monasteries. The short supply of liturgical books towards the end of the 15th century motivated Djurdje Crnoević to establish the first printing shop in the South Slavonic lands at Cetinje. During the first half of the 16th century there were several printing shops at Goražde, in the monastery of Rujan and in the monasteries Gračanica and Mileševa. An analysis of the production of all those printing shops show that exclusively books necessary for normal performance of the rite were printed.